2021
DOI: 10.20473/bhsj.v4i2.29762
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simvastatin and Virgin Coconut Oil (VCO) Combination Therapy as Triglyceride Plasma Lowering Agent in White Dyslipidemic Male Rat (Rattus norvegicus)

Abstract: Introduction: Dyslipidemia is a major health problem in Indonesia which leads to other diseases. Triglycerides (TG) is one of the increased lipid fractions which is related to dyslipidemia. Simvastatin is the main therapy in Indonesia to lower TG levels. The use of virgin coconut oil (VCO) becomes popular as a blood cholesterol-lowering agent even though the effects on TG level remains elusive. Since there is no empirical evidence VCO as a complementary therapy of simvastatin on TG levels, this experimental tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Virgin coconut oil (VCO) is a dietary supplement that has been shown to improve lipid profiles in dyslipidaemia diabetic rats by decreasing the total cholesterol (TC) and LDL [ 9 ]. An in vivo study confirmed that VCO could reduce the TG levels in the blood and be as effective as conventional therapy using simvastatin [ 10 ]. In a higher-level study, the intake of 30 mL of VCO daily increased HDL levels in healthy people [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virgin coconut oil (VCO) is a dietary supplement that has been shown to improve lipid profiles in dyslipidaemia diabetic rats by decreasing the total cholesterol (TC) and LDL [ 9 ]. An in vivo study confirmed that VCO could reduce the TG levels in the blood and be as effective as conventional therapy using simvastatin [ 10 ]. In a higher-level study, the intake of 30 mL of VCO daily increased HDL levels in healthy people [ 11 ].…”
Section: Introductionmentioning
confidence: 99%